Can God Create Abstract Objects? A Reply to Peter van Inwagen - Gould, Paul (Sophia, 2014)
The Platonic theist Peter van Inwagen argues that God cannot create abstract objects. Thus, the quantifier ‘everything’ in traditional statements of the doctrine of creation should be appropriately restricted to things that can enter into causal relations and abstract objects cannot: ‘God is the creator of everything distinct from himself…that can enter into causal relations.’ I respond to van Inwagen arguing that he has provided no good reason for thinking abstract objects must be uncreated. And if this is the case, then there is no good reason to think that God cannot create abstract objects.